Electronic Mortgage and the Vulnerability of Creditor Protection in Indonesia: Lessons from Supreme Court Decision No. 31K/TUN/2020 - Eka Sugiarti; Irene Eka Sihombing; Endang Pandamdari (Lembaga Riset Ilmiah, 2026)
This study examines the framework of legal protection afforded to creditors holding Electronic Mortgages (Hak Tanggungan Elektronik, HT-el) in Indonesia, with particular attention to its practical implementation, the legal difficulties it has generated including its bearing on Supreme Court Decision No. 31K/TUN/2020 and the design of an appropriate model for legal reform. A normative-juridical method with descriptive-analytical specifications was employed, complemented by a socio-legal approach drawing on library-based research and qualitative field interviews. The findings indicate that, although normative protection for HT-el holders has been established through the interplay of the Mortgage Law, the Electronic Information and Transactions Law, and related ministerial regulations, its practical application remains uneven and vulnerable to disruption. Because Indonesia's land registration system operates on a negative model with positive tendencies, electronic mortgage certificates may still be annulled where the underlying land title is administratively defective or subject to third-party claims. Compounding this vulnerability, technical shortcomings including server failures, erroneous data entry, and delays stemming from non-compliance with standard operating procedures can effectively downgrade a creditor's status from preferred to concurrent. In light of these findings, the study proposes a comprehensive legal reconstruction encompassing three dimensions: reform of legal substance, through amendment of the Mortgage Law to explicitly recognize digital records and clarify state liability; strengthening of legal structure, through enhanced infrastructural resilience and the establishment of dedicated oversight bodies; and cultivation of a digital legal culture among all stakeholders, so as to establish an electronic mortgage system that is both equitable and legally certain.